Fetoplacental cytogenetic discrepancy in a pregnancy with fetal mosaic tetrasomy 12p and Pallister-Killian syndrome detected by amniocentesis - Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Shih-Ting Lai; Tzu-Yun Chuang; Li-Feng Chen; Wayseen Wang (Elsevier, 2017)
Objective: We present fetoplacental cytogenetic discrepancy in a pregnancy with prenatally detected mosaic tetrasomy 12p by amniocentesis. Case report: A 34-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Cytogenetic analysis of cultured amniocytes revealed a karyotype of 47,XX,+i(12)(p10)[7]/46,XX[16]. Array comparative genomic hybridization (aCGH) analysis of the DNA extracted from cultured amniocytes revealed arr (12p)×3, (X)×2. Prenatal ultrasound findings were unremarkable. The pregnancy was subsequently terminated, and a fetus was delivered with facial dysmorphism consistent with the clinical features of Pallister-Killian syndrome (PKS). Postnatal cytogenetic analysis of the cultured cells from umbilical cord, skin, cord blood and placenta revealed 47,XX,+i(12)(p10)[6]/46,XX[34] in umbilical cord, 47,XX,+i(12)(p10)[11]/46,XX[29] in skin, 47,XX,+i(12)(p10)[3]/46,XX[47] in cord blood and 46,XX[40] in placenta. The mosaic tetrasomy 12p levels of the umbilical cord, skin, cord blood and placenta were 15%, 27.5%, 6% and 0%, respectively. aCGH analysis of the DNA extracted from uncultured cord blood and placenta revealed arr 12p13.33p11.1 (230,421-34,756,209)×3.0 in cord blood but no genomic imbalance in placenta. Polymorphic DNA marker analysis showed a maternal origin of the supernumerary isochromosome 12p in cord blood but biparental inheritance with equal fluorescent activity in placenta. Conclusion: Pregnancy with fetal PKS and mosaic tetrasomy 12p may present fetoplacental cytogenetic discrepancy. Therefore, genetic analysis on placenta alone may fail to detect fetal mosaic tetrasomy 12p associated with PKS.